2022
DOI: 10.1111/jocd.15561
|View full text |Cite
|
Sign up to set email alerts
|

Oral tranexamic acid in the treatment of hyperpigmentation disorder beyond melasma: A review

Abstract: Tranexamic acid (TA), a synthetic derivative of the amino acid lysine, is an antifibrinolytic, procoagulant agent that the Food and Drug Administration approves for the treatment of cyclic heavy menstrual bleeding and prevention of bleeding in patients with hemophilia undergoing tooth extractions. 1 Oral TA has been used off-label in dermatology in the treatment of melasma and other hyperpigmentation disorders. 2 In a recent study, oral TA has been reviewed thoroughly in treating melasma, and its effectiveness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…As a synthetic lysine analog antifibrinolytic agent, tranexamic acid competitively inhibits fibrinogen activation to fibrinolytic enzymes 11,65 . TXA also has anti‐inflammatory, antifibrotic, and antiangiogenic effects by strongly inhibiting fibrinolytic enzymes, which are important pathogenic mechanisms under the development of melasma 66 . Among them, the antiangiogenic effect of TA is associated with its ability to downregulate vascular endothelial growth factor and endothelin‐1 expression via fibrin.…”
Section: Discussionmentioning
confidence: 99%
“…As a synthetic lysine analog antifibrinolytic agent, tranexamic acid competitively inhibits fibrinogen activation to fibrinolytic enzymes 11,65 . TXA also has anti‐inflammatory, antifibrotic, and antiangiogenic effects by strongly inhibiting fibrinolytic enzymes, which are important pathogenic mechanisms under the development of melasma 66 . Among them, the antiangiogenic effect of TA is associated with its ability to downregulate vascular endothelial growth factor and endothelin‐1 expression via fibrin.…”
Section: Discussionmentioning
confidence: 99%
“…2 Oral tranexamic acid (TXA), an antifibrinolytic and procoagulant agent has been used off-label in the treatment of hyperpigmentary diseases. [3][4][5][6] The inhibitory effect of TXA on plasmin activation is thought to further interfere with the release of inflammatory factors (α-arachidonic acid and prostaglandin E2) and angiogenic factors (vascular endothelial growth factor [VEGF] and endothelin-1 [ET-1]), resulting in the reduction of melanogenesis and vascularization in the pathogenesis of hyperpigmentary disorders. 7,8 Few case reports and pilot studies demonstrated the efficacy of intense pulsed light (IPL) in the treatment of Riehl's melanosis.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its historical hemostatic indications at higher doses, multiple studies have demonstrated low clotting risk when TA is used at dosages used for dermatologic indications. [2][3][4] For example, the largest retrospective review of oral TA for melasma found that among 561 included patients, only 1 (who was later found to have protein S deficiency) developed a deep vein thrombosis. 4 Likewise, in a 5-year single-institution crosssectional study of 206 patients with 451 prescriptions of TA, 650 mg, once daily, we found no documented adverse events that were associated with clotting risk.…”
mentioning
confidence: 99%
“…[2][3][4] For example, the largest retrospective review of oral TA for melasma found that among 561 included patients, only 1 (who was later found to have protein S deficiency) developed a deep vein thrombosis. 4 Likewise, in a 5-year single-institution crosssectional study of 206 patients with 451 prescriptions of TA, 650 mg, once daily, we found no documented adverse events that were associated with clotting risk. 2 This included durations of therapy of up to 6 months without follow-up study.…”
mentioning
confidence: 99%
See 1 more Smart Citation